The Impact of Market Relocation to Roadway and Sidewalk Functions at Patiunus Street Pekalongan - Rany, Azhar Hasna; Rukayah, R Siti; Sari, Suzzana Ratih (Universitas Negeri Semarang, 2021)
Abstract: The more advance establishment of the country leads to the more developed economic progress. The economic activities require better supporting facilities and infrastructure. Market is one of infrastructure that can support economic activities. In addition, it requires a market location, it also requires a road to distribute the commodities in or out of the city. Roadway and sidewalk are supporting infrastructures that improve the economy in a country. One of market in Pekalongan city, Banjarsari Market’s was in fire. Then Banjarsari market was relocated in Patiunus Street. This research was conducted in Patiunus street, the sidewalk that was used for Banjarsari market relocation. The market relocation in the roadway and sidewalks can affect road functions and road users’ activities. Especially in the balancing interaction factor between the pedestrians and the vehicles, the safety factor of adequate space for pedestrians, the facilities offered a pleasurable experience on the sidewalk, the availability of public facilities unites, becomes supporting elements of the sidewalk. This research used the qualitative method and used three data collection techniques: direct observation, questionnaire, and documentation. The conclusion of this study is the existence of the Banjarsari market relocation on Jalan Patiunus affected the function of roads and sidewalks. By analyzing the result of the field survey and questionnaire to the road user and sidewalk users from Patiunus street, it can be concluded that the four standards for sidewalk (the balancing interaction between the pedestrians and the vehicles, safety factor, the facilities offered a pleasurable experience on the sidewalk and the availability of public facilities unites and becomes supporting elements of the sidewalk). Therefore, Patiunus street can have good functions for road user and sidewalk users.